Building bridges a comparative analysis of outreach programs of public city libraries in the National Capital Region - Valila, Nadeshya T. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Public libraries have vital roles in the provision of necessary knowledge to satisfy the information needs of the community they are serving. They are also bound to develop the literacy of the people in their community by innovating programs that will attract the people to use the library services. This include conducting outreach programs, to further ensure that all sectors are equally tapped and being provided opportunities and services by the public libraries. This study aimed to identify the existing outreach programs. That are being conducted by different public city libraries in the National Capital Region. The data gathered were compared and analyzed to ferret out the best practices, which can, later on, be adopted by other institutions without outreach programs.